Ocena jakości usług ubezpieczeniowych świadczonych przez agentów - Jędrzychowska, Anna (Evaluation of Quality of Services Offered by Insurance Brocers, 2007)
The article is an attempt to supplement a complex evaluation of insurance brocers as regards the services they offer. In rating evaluation, apart from the ability of an insurance company to fulfill the insurance deal. The paper consists in an analysis of evaluation of quantity of services offered by insurance companies. To show it, I used a questionnaire completed by 180 extramural students of economy, who declared to have sufficient knowledge on insurance and to be receivers of insurance goods. The questionnaire analyses the offer of insurance companies, the insurance company insurance system, employee training, professional ethics and sophistication. General evaluation of insurance companies is the final outcome of the paper. To carry out the research I used the 9 grades Likert Scale (from 'very bad grade' to 'very good grade'). In the analysis I use the factor analysis, evaluate the dependence between the single evaluations (i.e. their influence on the general evaluation) and show those elements of the work of insurance companies that according to respondents have the greater influence on how they perceive the services offered by insurance companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 587-596